Racial integration through two-way dual language immersion: A case study - Uzzell, Elizabeth M.; Ayscue, Jennifer B. (Education Policy Analysis Archives, 2021)
Despite increasingly diverse public school enrollment, students across the U.S. are still segregated by race and poverty, and English learners (ELs) often experience triple segregation by race, poverty, and language. Two-way immersion (TWI) programs may create racially integrated learning environments, by offering a dual language model that balances native English speakers and speakers of the partner language. Through semi-structured interviews, observation, and document analysis, this qualitative case study examined how a Spanish TWI program facilitates integration in a rural elementary school. Findings show that students from different backgrounds may have equal status in mutually beneficial environments, can become bilingual and bicultural, and may experience lifelong benefits. Implications include the need for increased federal, state, and local funding to support districts using TWI to achieve integration as well as a federal language policy that promotes TWI. <!--[if !supportLineBreakNewLine]--> <!--[endif]-->